Motivation and success factors in radiological research in Germany – results of a survey by the Methodology and Research Working Group of the German Radiological Society - Wegner, Franz; Heinrichs, Helen; Stahlmann, Katharina; Molwitz, Isabel; Keller-Yamamura, Sarah; Kloeckner, Roman; Barkhausen, Jörg; Bäuerle, Tobias; Cyran, Clemens C; Dietzel, Matthias; Eisenblätter, Michel; Hilger, Ingrid; Jung, Caroline; Schick, Fritz; Kiessling, Fabian; Bannas, Peter (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Investigation of motivation and identification of success factors in radiology research in Germany.Using a German online survey (54 questions, period: 3.5 months), demographic aspects, intrinsic and extrinsic success characteristics, as well as personal and organizational success factors were surveyed based on a career success model. The survey results were reported descriptively. The correlations between success factors and success characteristics were examined using linear, binary-logistic, and multinomial regression models.176 people (164 academically active, 10 not academically active) answered the survey. Most participants (80%, 139/174) worked at a university hospital. 32% had privatdozent or professor as their highest academic title (56/173). The researchers' main motivation was intrinsic interest in research (55%, 89/163), followed by a desire to increase their own career opportunities (25%, 41/163). The following were identified as factors for intrinsic success: i) support from department management (estimate=β=0.26, p<0.001), ii) good work-life balance (β=0.37, p<0.001), and iii) the willingness to pursue science even after reaching the career goal (β=0.16, p<0.016). Relevant factors for extrinsic scientific success were mentoring, protected research time, and activities in professional societies.Researchers in German radiology are mainly intrinsically motivated. Factors known from the literature that determine intrinsic and extrinsic scientific success were confirmed in this study. Knowledge of these factors allows targeted systematic support and could thus increase scientific success in German radiology.Untersuchung der Motivation und Identifikation von Erfolgsfaktoren in der radiologischen Forschung in Deutschland.Mittels einer deutschsprachigen Online-Umfrage (54 Fragen, Zeitraum: 3,5 Monate) wurden demografische Aspekte, intrinsische und extrinsische Erfolgsmerkmale sowie persönliche und organisatorische Erfolgsfaktoren auf Basis eines Karriere-Erfolgsmodells abgefragt. Die Umfrageergebnisse wurden deskriptiv beschrieben. Die Zusammenhänge zwischen Erfolgsfaktoren und Erfolgsmerkmalen wurden anhand linearer, binär-logistischer und multinominaler Regressionsmodelle untersucht.176 Personen (164 wissenschaftlich Aktive, 10 nicht wissenschaftlich Aktive) haben an der Umfrage teilgenommen. Die Mehrheit der Teilnehmenden (80%, 139/174) war an einer Universitätsklinik tätig. 32% hatten als höchsten akademischen Titel einen Privatdozenten- oder Professorentitel (56/173). Die Hauptmotivation der Forschenden war intrinsisches Forschungsinteresse (55%, 89/163) gefolgt von der Steigerung der eigenen Karrierechancen (25%, 41/163). Als Faktoren für intrinsischen Erfolg wurden identifiziert: i) Unterstützung durch die Abteilungsleitung (Estimate=β=0,26, p<0,001), ii) gute Work-Life-Balance (β=0,37, p<0,001) sowie iii) die Bereitschaft, Wissenschaft auch nach Erreichen des Karriereziels auszuüben (β=0,16, p<0,016). Relevante Faktoren für extrinsischen wissenschaftlichen Erfolg waren Mentoring, regelmäßige Freistellungstage und fachgesellschaftliches Engagement.Forschende in der deutschen Radiologie sind hauptsächlich intrinsisch motiviert. Aus der Literatur bekannte Faktoren, die intrinsischen und extrinsischen wissenschaftlichen Erfolg bedingen, konnten in dieser Arbeit bestätigt werden. Die Kenntnis dieser Faktoren erlaubt eine gezielte systematische Förderung und könnte so den wissenschaftlichen Erfolg in der deutschen Radiologie steigern.
Keywords: success factors; scientific success; survey; radiological research